Titanium alloy water-based cutting fluid of Ti3C2Tx-coated TiO2 composite particles as well as preparation method and application of titanium alloy water-based cutting fluid

By using hydrothermal synthesis method to generate Ti3C2Tx@TiO2 composite nanoparticles in the water-based cutting fluid of titanium alloy, the problems of low thermal conductivity and poor lubrication effect during the cutting process of titanium alloy are solved, and more efficient cooling and lubrication effects are achieved, reducing the number of Tool wear.

CN119505987APending Publication Date: 2025-02-25NANCHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411534299.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

During the cutting process, titanium alloy has low thermal conductivity, which makes cutting heat difficult to transfer, resulting in serious tool wear and high processing costs. Traditional oil-based cutting fluid has limited lubrication effect on titanium alloys, while water-based cutting fluid has poor lubrication and anti-rust effects.

Method used

TiO2 nanoparticles were generated on the surface of Ti3C2Tx nanosheets by hydrothermal synthesis, and Ti3C2Tx@TiO2 composite nanoparticles were prepared to prevent TiO2 nanoparticles from agglomeration and improve the lubricating performance of water-based cutting fluid.

Benefits of technology

It effectively improves the lubricating performance of titanium alloy water-based cutting fluid, reduces friction and wear, reduces tool wear, and improves the cooling and lubrication effect of titanium alloy processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505987A_ABST
    Figure CN119505987A_ABST
Patent Text Reader

Abstract

The invention provides a titanium alloy water-based cutting fluid of Ti3C2Tx-coated TiO2 composite particles as well as a preparation method and application of the titanium alloy water-based cutting fluid, and relates to the technical field of cutting fluid preparation. According to the titanium alloy water-based cutting fluid, TiO2 nano-particles are generated on the surfaces of Ti3C2Tx nanosheets through hydro-thermal synthesis, Ti3C2Tx-coated TiO2 composite nano-particles capable of effectively preventing aggregation of the TiO2 nano-particles are prepared, meanwhile, the lubricating performance of the cutting fluid can be further improved through the synergistic effect of the Ti3C2Tx nanosheets and the TiO2 nano-particles, and the titanium alloy water-based cutting fluid takes water as a main body, so that the titanium alloy water-based cutting fluid has the beneficial effects that the titanium alloy water-based cutting fluid is environmentally friendly, and the service life of the titanium alloy water-based cutting fluid is prolonged. The lubricant is good in cooling effect, easy to clean, free of pollution to the environment and harmless to human health, and belongs to an environment-friendly lubricant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cutting fluid preparation, and in particular to a Ti3C2T x @TiO2 composite particle titanium alloy water-based cutting fluid and its preparation method and application. Background Art

[0002] As a new type of lightweight alloy, titanium alloy has excellent physical and mechanical properties such as high specific strength, good corrosion resistance and high heat resistance. Among them, Ti6Al4V (TC4) is the most widely used titanium alloy. With the continuous development of titanium alloy processing technology, its application has expanded to shipbuilding, chemical industry, automobile and medical equipment. However, titanium alloy is a typical difficult-to-process metal. Due to the low thermal conductivity and small elastic modulus of titanium alloy, a large amount of cutting heat will be generated during the cutting of titanium alloy, but the cutting heat is difficult to transfer, resulting in temperature rise and severe tool wear, which leads to high processing costs.

[0003] Traditional oil-based cutting fluids have small specific heat capacity and limited thermal conductivity, which can easily cause a large amount of cutting heat to be generated in the cutting area, resulting in severe tool wear and a significant increase in cutting costs. At the same time, their lubrication effect on titanium alloys is limited. Compared with oil-based cutting fluids, water-based cutting fluids have better cooling performance, are easy to clean, non-flammable, and are more friendly to the environment and human health, but their lubrication and rust prevention effects are poor. Nanoparticles can convert sliding friction on the surface of the friction pair into rolling friction, while playing a supporting role, and can melt or sinter at the friction cracks in the friction contact area of ​​high temperature and high pressure, play a repairing role, and even produce mechanical polishing or form a deposition film in the friction contact area. Research on nanoparticles suitable for enhancing the efficiency of water-based cutting fluids is of great significance to improving the cooling and lubrication effect of titanium alloy processing.

[0004] Nanoparticles of TiO2 are widely used in the field of lubricant additives due to their high hardness and surface activity. They show excellent anti-wear properties. For TC4 titanium alloy, TiO2 nanoparticles promote and supplement the formation of friction oxide film, thereby effectively reducing the friction coefficient. However, the dispersibility of TiO2 in water-based lubricants is limited, and it is easy to agglomerate, resulting in deterioration of lubrication performance.

[0005] Therefore, it is urgent to provide a solution to solve the above problems. Summary of the invention

[0006] The present invention aims to provide a Ti3C2T x @TiO2 composite particles titanium alloy water-based cutting fluid and its preparation method and application, the titanium alloy water-based cutting fluid is synthesized by hydrothermal synthesis on Ti3C2T xTiO2 nanoparticles are generated on the surface of nanosheets, and Ti3C2T3O2 nanoparticles can be prepared to effectively prevent the agglomeration of TiO2 nanoparticles. x @TiO2 composite nanoparticles, while Ti3C2T x The nanosheets and TiO2 nanoparticles produce a synergistic lubrication effect, further improving the lubrication performance of the water-based cutting fluid.

[0007] In a first aspect, the present invention provides a Ti3C2T x The titanium alloy water-based cutting fluid with TiO2 composite particles includes the following components: 15 to 30 parts of Ti3C2T x @TiO2 composite particles, 10 to 25 parts of dispersant, 2 to 10 parts of defoamer, 2 to 5 parts of rust inhibitor, 5 to 10 parts of pH regulator and 450 to 500 parts of deionized water.

[0008] The titanium alloy water-based cutting fluid provided by the invention is mainly water-based, has good cooling effect, is easy to clean, has no pollution to the environment, is harmless to human health, and is an environmentally friendly lubricant.

[0009] Optionally, the dispersant includes at least one of polyethylene glycol, sodium lauryl sulfate, fatty alcohol polyoxyethylene ether and sodium hexametaphosphate.

[0010] Optionally, the defoaming agent includes at least one of polydimethylsiloxane, fluorosilicone, organic modified siloxane, polyether, polyoxypropylene, higher carbon alcohol and higher carbon alcohol fatty acetic acid complex.

[0011] Optionally, the rust inhibitor includes at least one of sodium carbonate, sodium phosphate, monoethanolamine, diethanolamine, triethanolamine and amide.

[0012] Optionally, the pH adjuster includes at least one of diglycolamine, diisopropanolamine, ammonia water and tetraethylammonium hydroxide.

[0013] The addition of rust inhibitors and pH adjusters is beneficial to inhibit the corrosion of cutting tools, machine tools and workpieces, and can inhibit the growth of bacteria.

[0014] In a second aspect, the present invention provides a Ti3C2T x A method for preparing a titanium alloy water-based cutting fluid containing TiO2 composite particles comprises the following steps:

[0015] Ti3C2T x @TiO2 composite particles are stirred and dissolved in water, then centrifuged and the upper solution is collected;

[0016] Dispersant, defoamer and rust inhibitor were added to the upper solution, and the pH was adjusted after ultrasound to obtain Ti3C2T x @TiO2 composite particles of titanium alloy water-based cutting fluid.

[0017] Optionally, the stirring time is 1 h to 3 h.

[0018] Optionally, the centrifugation comprises centrifugation at 800 rpm to 2500 rpm for 25 min to 45 min.

[0019] Optionally, the ultrasound comprises water bath ultrasound at 25° C. to 45° C. for 1 h to 4 h.

[0020] Ultrasonic process can promote the dispersant to Ti3C2T x @TiO2 nanosheets are effectively wrapped to prevent the agglomeration and sedimentation of particles. The Ti3C2T x @TiO2 composite particle material has good dispersibility, which is conducive to fully exerting its lubrication and thermal conductivity properties.

[0021] Optionally, adjusting the pH includes adjusting the pH value to 8.0-10.0 using a pH adjuster.

[0022] Specifically, the Ti3C2T x The preparation of TiO2 composite particle material includes the following steps:

[0023] (1) Under water bath conditions, the etchant and the precursor are mixed and stirred, and then centrifuged and washed until the pH of the supernatant is neutral, and the bottom precipitate is collected to obtain Ti3C2T x ;

[0024] (2) Ti3C2T x After ultrasonic stripping in the intercalant, the mixture was centrifuged at low speed, the supernatant was centrifuged at high speed, and the bottom precipitate was collected after freeze drying to obtain Ti3C2T x Nanosheets;

[0025] (3) Ti3C2T x The nanosheets were dispersed in water for hydrothermal reaction, and the precipitate was collected by freeze drying to obtain Ti3C2T x @TiO2 composite particle material.

[0026] Ti3C2T x Nanosheets have the advantages of easy shearing between layers, small size, large specific surface area and good carrying capacity. At the same time, the hydrophilic functional groups on the surface can enable them to maintain good dispersion in water, and their unique layer structure can promote interlayer sliding and thus reduce friction.

[0027] Optionally, in step (1), the temperature of the water bath is 30°C to 50°C.

[0028] Optionally, in step (1), the etchant includes 7 mol / L to 10 mol / L hydrochloric acid solution and 35% to 45% hydrofluoric acid solution or 0.04 g / mL to 0.09 g / mL lithium fluoride.

[0029] Optionally, in step (1), the precursor includes any one of titanium silicon carbide and titanium aluminum carbide.

[0030] Optionally, in step (1), the mass volume ratio of the precursor to the etchant is (0.08-0.15) g:1 mL.

[0031] Optionally, in step (1), the mixing and stirring time is 24h to 48h.

[0032] Optionally, in step (1), the centrifugal rotation speed is 5000 rpm to 9000 rpm.

[0033] Optionally, in step (2), the intercalation agent comprises any one of a 97% to 99% dimethyl sulfoxide solution and a 5% to 25% tetramethylammonium hydroxide solution.

[0034] Optionally, in step (2), the Ti3C2T x The mass volume ratio of the intercalant is (0.07-0.12) g:1 mL.

[0035] Optionally, in step (2), the ultrasonic stripping time is 1 h to 3 h.

[0036] Optionally, in step (2), the low-speed centrifugation includes centrifugation at 1000 rpm to 3000 rpm for 30 min to 60 min.

[0037] Optionally, in step (2), the high-speed centrifugation includes centrifugation at 9000 rpm to 11000 rpm for 30 min to 60 min.

[0038] Optionally, in step (3), the Ti3C2T x The mass volume ratio of the nanosheets to the water is (0.017-0.03) g:1 mL.

[0039] Optionally, in step (3), the hydrothermal reaction comprises reacting at 180°C to 200°C for 12h to 36h.

[0040] Preparation of Ti3C2T by hydrothermal synthesis x @TiO2 composite particles, Ti3C2T x TiO2 can be generated in situ as a titanium source without the introduction of other substances, and the friction oxide film containing TiO2 generated on the surface of titanium alloy can effectively reduce friction and wear. xAnd TiO2 play a role in supplementing the formation of friction oxide film during the friction process.

[0041] Optionally, in step (3), the freeze-drying time is 24 h to 36 h.

[0042] In a third aspect, the present invention provides an application of the titanium alloy water-based cutting fluid in the lubrication process of titanium alloy cutting.

[0043] When the titanium alloy water-based cutting fluid is used as a lubricant in titanium alloy processing, the occurrence of friction and wear can be effectively reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly introduce the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments.

[0045] Figure 1 Ti3C2T prepared in Example 1 x @SEM image of titanium alloy water-based cutting fluid with TiO2 composite particles;

[0046] Figure 2 Ti3C2T prepared in Example 3 x @SEM image of titanium alloy water-based cutting fluid with TiO2 composite particles;

[0047] Figure 3 The Ti3C2T prepared in Examples 1 to 4 in the performance test x @The friction coefficient of the titanium alloy water-based cutting fluid with TiO2 composite particles and the surface of the Ti6Al4V titanium alloy disk under lubrication of the control group;

[0048] Figure 4 The SEM image of the wear of Ti6Al4V titanium alloy disk under control group lubrication;

[0049] Figure 5 Ti3C2T prepared in Example 1 x @SEM image of wear of Ti6Al4V titanium alloy disk lubricated by water-based cutting fluid of titanium alloy with TiO2 composite particles;

[0050] Figure 6 Ti3C2T prepared in Example 3 x SEM image of wear of Ti6Al4V titanium alloy disk lubricated by water-based cutting fluid of titanium alloy with @TiO2 composite particles. DETAILED DESCRIPTION

[0051] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention will be further described through the following embodiments in conjunction with the accompanying drawings. However, the following embodiments are illustrative and are only used to specifically describe the present invention rather than to limit the present invention.

[0052] The present invention provides a Ti3C2T x The titanium alloy water-based cutting fluid with TiO2 composite particles includes the following components: 15 to 30 parts of Ti3C2T x @TiO2 composite particles, 10 to 25 parts of dispersant, 2 to 10 parts of defoamer, 2 to 5 parts of rust inhibitor, 5 to 10 parts of pH regulator and 450 to 500 parts of deionized water.

[0053] In some embodiments, the dispersant includes at least one of polyethylene glycol, sodium lauryl sulfate, fatty alcohol polyoxyethylene ether, and sodium hexametaphosphate.

[0054] In some embodiments, the defoaming agent includes at least one of polydimethylsiloxane, fluorosilicone, organic modified siloxane, polyether, polyoxypropylene, higher alcohol and higher alcohol fatty acetic acid complex.

[0055] In some embodiments, the rust inhibitor includes at least one of sodium carbonate, sodium phosphate, monoethanolamine, diethanolamine, triethanolamine, and amide.

[0056] In some embodiments, the pH adjuster includes at least one of diglycolamine, diisopropanolamine, ammonia and tetraethylammonium hydroxide.

[0057] The present invention also provides a Ti3C2T x A method for preparing a titanium alloy water-based cutting fluid containing TiO2 composite particles comprises the following steps:

[0058] S1. Ti3C2T x @TiO2 composite particles are stirred and dissolved in water, then centrifuged and the upper solution is collected;

[0059] S2, dispersant, defoamer and rust inhibitor were added to the upper solution, and pH was adjusted after ultrasound to obtain Ti3C2T x @TiO2 composite particles of titanium alloy water-based cutting fluid.

[0060] In some embodiments, when performing step S1, the stirring time is 1 hour to 3 hours.

[0061] In some embodiments, when performing step S1, the centrifugation includes centrifugation at 800 rpm to 2500 rpm for 25 min to 45 min.

[0062] In fact, when executing step S1, the following sub-steps are included:

[0063] S1.1 Etching: Mix the etchant and the precursor in a water bath, centrifuge and wash until the pH of the supernatant is neutral, collect the bottom precipitate, and obtain Ti3C2T x ;

[0064] S1.2, peeling: Ti3C2T x After ultrasonic stripping in the intercalant, the mixture was centrifuged at low speed, the supernatant was centrifuged at high speed, and the bottom precipitate was collected after freeze drying to obtain Ti3C2T x Nanosheets;

[0065] S1.3, hydrothermal synthesis: Ti3C2T x The nanosheets were dispersed in water and subjected to hydrothermal reaction. The precipitate was collected by freeze drying to obtain Ti3C2T x @TiO2 composite particle material.

[0066] In some embodiments, when performing step S1.1, the temperature of the water bath is 30°C to 50°C.

[0067] In some embodiments, when performing step S1.1, the etchant includes 7 mol / L to 10 mol / L hydrochloric acid solution and 35% to 45% hydrofluoric acid solution or 0.04 g / mL to 0.09 g / mL lithium fluoride.

[0068] In some embodiments, when performing step S1.1, the precursor includes any one of titanium silicon carbide and titanium aluminum carbide.

[0069] In some embodiments, when performing step S1.1, the mass volume ratio of the precursor to the etchant is (0.08-0.15) g:1 mL.

[0070] In some embodiments, when performing step S1.1, the mixing and stirring time is 24h to 48h.

[0071] In some embodiments, when performing step S1.1, the centrifugal rotation speed is 5000 rpm to 9000 rpm.

[0072] In some embodiments, when performing step S1.2, the intercalant comprises any one of a 97% to 99% dimethyl sulfoxide solution and a 5% to 25% tetramethylammonium hydroxide solution.

[0073] In some embodiments, when performing step S1.2, the Ti3C2T x The mass volume ratio of the intercalant is (0.07-0.12) g:1 mL.

[0074] In some embodiments, when performing step S1.2, the ultrasonic peeling time is 1 hour to 3 hours.

[0075] In some embodiments, when performing step S1.2, the low-speed centrifugation includes centrifugation at 1000 rpm to 3000 rpm for 30 min to 60 min.

[0076] In some embodiments, when performing step S1.2, the high-speed centrifugation includes centrifugation at 9000 rpm to 11000 rpm for 30 min to 60 min.

[0077] In some embodiments, when performing step S1.3, the Ti3C2T x The mass volume ratio of the nanosheets to the water is (0.017-0.03) g:1 mL.

[0078] In some embodiments, when performing step S1.3, the hydrothermal reaction includes reacting at 180°C to 200°C for 12h to 36h.

[0079] In some embodiments, when performing step S1.3, the freeze-drying time is 24 hours to 36 hours.

[0080] In some embodiments, when performing step S2, the ultrasonication includes water bath ultrasonication at 25°C to 45°C for 1 hour to 4 hours.

[0081] In some embodiments, when performing step S2, adjusting the pH includes adjusting the pH value to 8.0-10.0 using a pH adjusting agent.

[0082] The invention also provides an application of the titanium alloy water-based cutting fluid in the lubrication process of titanium alloy cutting processing.

[0083] Example 1

[0084] Embodiment 1 of the present invention provides a Ti3C2T x A method for preparing a titanium alloy water-based cutting fluid containing TiO2 composite particles comprises the following steps:

[0085] S1.1. In a 40℃ water bath, 2g of titanium silicon carbide powder was mixed with 10mL of 35% hydrofluoric acid and 10mL of 7mol / L hydrochloric acid solution and stirred for 24h. The mixture was centrifuged at 6000rpm until the pH of the supernatant was close to neutral. The bottom precipitate was collected to obtain 1.8g of layered Ti3C2T x ;

[0086] S1.2, 1.8g layered Ti3C2T x30 mL of 7.5% tetramethylammonium hydroxide solution was added, and the mixture was subjected to ultrasonic stripping in an ice-water bath for 2 h. The mixture was centrifuged at 2000 rpm for 30 min, and the supernatant was centrifuged at 10000 rpm for 30 min. The precipitate was collected after freeze drying for 48 h to obtain 1 g of two-dimensional Ti3C2T x Nanosheets;

[0087] S1.3, 1g of two-dimensional Ti3C2T x The nanosheets were dispersed in 30 mL of deionized water, placed in a reactor for hydrothermal reaction at 180 °C for 12 h, and then freeze-dried in vacuum for 24 h to obtain Ti3C2T x @TiO2 composite particle material;

[0088] S2, 1.2g Ti3C2T x The TiO2 composite particles were mechanically stirred with 360 mL of deionized water for 1 h, and then centrifuged at 1500 rpm for 30 min to collect the upper solution. 0.8 g of sodium lauryl sulfate, 0.2 g of emulsified silicone oil, and 0.4 g of sodium carbonate were added to the upper solution, and after ultrasonication at 25 °C for 2 h, 0.6 g of diglycolamine was added to adjust the pH to 8.0 to obtain Ti3C2T x @TiO2 composite particles of titanium alloy water-based cutting fluid.

[0089] The prepared Ti3C2T x SEM characterization of titanium alloy water-based cutting fluid with @TiO2 composite particles, such as Figure 1 As shown in the figure, it is found that its size is about 200nm, surrounded by TiO2 particles of about 50nm, indicating that Ti3C2T x @TiO2 nanosheets showed no obvious tendency to agglomerate, proving that the hydrothermal reaction proceeded relatively fully.

[0090] Example 2

[0091] Embodiment 2 of the present invention provides a Ti3C2T x The method for preparing a titanium alloy water-based cutting fluid with @TiO2 composite particles is different from that in Example 1 in that:

[0092] In step S1.1: the concentration of hydrofluoric acid is 40%, and the centrifugal speed is 7000 rpm;

[0093] In step S1.2: the concentration of the tetramethylammonium hydroxide solution is 5%;

[0094] In step S1.3: the hydrothermal reaction conditions are 185°C for 18h;

[0095] Step S2: Added Ti3C2T x@The TiO2 composite particle material is 1.2 g, the centrifugal condition is 2000 rpm for 40 min, the added dispersant is 0.8 g sodium dodecyl sulfate, the added defoaming agent is 0.4 g polyether monosiloxane, the added rust inhibitor is 0.3 g sodium chromate, the water bath ultrasound time is 3 h, and the added pH adjuster is 0.5 g diisopropanolamine.

[0096] Example 3

[0097] Embodiment 3 of the present invention provides a Ti3C2T x The method for preparing a titanium alloy water-based cutting fluid with TiO2 composite particles is different from that in Example 1 in that:

[0098] In step S1.1: the added precursor is 2 g of titanium aluminum carbide, the added etchant is a solution of 3 g of lithium fluoride and 35 mL of 9 mol / L hydrochloric acid, and the stirring time is 36 h;

[0099] In step S1.2: the intercalant added is 20 mL of 99% dimethyl sulfoxide solution, the time of ultrasonic stripping in an ice-water bath is 1 h, the condition of high-speed centrifugation is 9000 rpm for 40 min, and the time of freeze drying is 36 h;

[0100] In step S1.3: the hydrothermal reaction conditions are 190°C for 18h;

[0101] Step S2: Added Ti3C2T x @The amount of TiO2 composite particle material was 1.2 g, the added dispersant was 0.8 g polyethyleneimine, the added defoaming agent was 0.3 g polydimethylsiloxane, the added rust inhibitor was 0.4 g sodium phosphate, the water bath ultrasound time was 3 h, the added pH adjuster was 0.4 g diisopropanolamine, and the pH was adjusted to 9.0.

[0102] The prepared Ti3C2T x SEM characterization of titanium alloy water-based cutting fluid with @TiO2 composite particles, such as Figure 2 As shown, its size is found to be around 500nm, indicating that Ti3C2T x @TiO2 nanosheets agglomerate, which may be due to insufficient exfoliation caused by short ice-water bath ultrasonication time, and too long hydrothermal reaction time causing too many TiO2 particles to adhere to Ti3C2T x Nanosheet surface.

[0103] Example 4

[0104] Embodiment 4 of the present invention provides a Ti3C2T x The method for preparing a titanium alloy water-based cutting fluid with TiO2 composite particles is different from that in Example 1 in that:

[0105] In step S1.1: the added precursor is 4 g of titanium aluminum carbide, the added etchant is a solution of 6 g of lithium fluoride and 80 mL of 9 mol / L hydrochloric acid, and the stirring time is 36 h;

[0106] In step S1.2: the intercalant added is 40 mL of 99% dimethyl sulfoxide solution, the speed of high-speed centrifugation is 9000 rpm, and the freeze-drying time is 36 h;

[0107] In step S1.3: the hydrothermal reaction conditions are 200°C for 24 hours, and the vacuum freeze-drying time is 36 hours;

[0108] In step S2: 2.4 g of Ti3C2Tx@TiO2 composite particle material was added, 1.6 g of fatty alcohol polyoxyethylene ether was added as the dispersant, 0.8 g of organic modified siloxane was added as the defoaming agent, 0.8 g of sodium silicate was added as the rust inhibitor, the water bath ultrasound time was 3 h, 0.8 g of tetramethylammonium hydroxide was added as the pH adjuster, and the pH was adjusted to 9.0.

[0109] Performance Testing

[0110] The Ti3C2T prepared in Examples 1 to 4 x The titanium alloy water-based cutting fluid with @TiO2 composite particles was used to detect the friction reduction and anti-wear effect on the surface of Ti6Al4V titanium alloy (diameter 24mm, hardness 34HRC) disk under the UMT-3 friction tester, and deionized water was used as a control.

[0111] For the friction pair, a YG8 steel ball with a diameter of 10 mm and a hardness of 89 HRA was selected. The sliding mode was rotary, the rotation speed was 200 rpm, the rotation radius was 4 mm, the load was 5 N, and the test time was 10 min. Before the test, 1 mL / mm 2 The lubricants are not replenished during the subsequent sliding process.

[0112] Figure 3 is the friction coefficient of the Ti6Al4V titanium alloy disk surface under lubrication of each embodiment and the control group. The results show that the friction coefficient of each embodiment is significantly lower than that of the control group. At the same time, the friction coefficient of the control group increases significantly with the passage of sliding time. After sliding for 85 seconds, the friction coefficient is as high as 0.45. The friction coefficient of Example 1 is stable at about 0.17 during the sliding process. The friction coefficient of Example 3 fluctuates more significantly, between 0.17 and 0.3.

[0113] The SEM images of the wear conditions of the Ti6Al4V titanium alloy disks under lubrication of the control group, Example 1 and Example 3 are shown in Figure 2. Figures 4 to 6As shown in the figure, by comparison, it is found that the surface of the Ti6Al4V titanium alloy disk under the lubrication of the control group is severely worn and there are a lot of adhesions. The main wear mechanism is severe adhesive wear. The wear scar surface of the Ti6Al4V titanium alloy disk under the lubrication of Example 1 is obviously smoother, with only a small amount of wear debris and no block adhesions. This is because in the Ti3C2T x @TiO2, Ti3C2T x The unique lamellar structure promotes interlayer sliding and reduces friction. In addition, the TiO2 nanoparticles play a ball bearing effect and self-repairing role, which reduces the wear on the surface of the Ti6Al4V titanium alloy disk. The wear marks on the friction surface of the Ti6Al4V titanium alloy disk under lubrication in Example 3 are deeper than those in Example 1, indicating that the wear is more serious. Figure 1 and Figure 2 It is speculated that the Ti3C2T in Example 3 x @TiO2 agglomerates, making it difficult for it to enter the friction pair and play a lubricating role during the friction process.

[0114] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.

Claims

1. A Ti3C2T x @TiO2 composite particles titanium alloy water-based cutting fluid, characterized in that, It includes the following components: 15-30 parts Ti3C2T x @TiO2 composite particles, 10 to 25 parts of dispersant, 2 to 10 parts of defoamer, 2 to 5 parts of rust inhibitor, 5 to 10 parts of pH regulator and 450 to 500 parts of deionized water.

2. The titanium alloy water-based cutting fluid according to claim 1, characterized in that: The dispersant includes at least one of polyethylene glycol, sodium lauryl sulfate, fatty alcohol polyoxyethylene ether and sodium hexametaphosphate; and / or the defoamer includes at least one of polydimethylsiloxane, fluorosilicone, organic modified siloxane, polyether, polyoxypropylene, high carbon alcohol and high carbon alcohol fatty acetic acid complex; and / or the rust inhibitor includes at least one of sodium carbonate, sodium phosphate, monoethanolamine, diethanolamine, triethanolamine and amide; the pH adjuster includes at least one of diglycolamine, diisopropanolamine, ammonia water and tetraethylammonium hydroxide.

3. A Ti3C2T x A method for preparing a titanium alloy water-based cutting fluid containing TiO2 composite particles, characterized in that: The following steps are involved: Ti3C2T x @TiO2 composite particles are stirred and dissolved in water, then centrifuged and the upper solution is collected; Dispersant, defoamer and rust inhibitor were added to the upper solution, and the pH was adjusted after ultrasound to obtain Ti3C2T x @TiO2 composite particles of titanium alloy water-based cutting fluid.

4. The preparation method according to claim 3, characterized in that: The stirring time is 1h to 3h; the centrifugation includes centrifugation at 800rpm to 2500rpm for 25min to 45min; the ultrasound includes water bath ultrasound at 25℃ to 45℃ for 1h to 4h; the pH adjustment includes adjusting the pH value to 8.0 to 10.0 with a pH adjuster.

5. The preparation method according to claim 3, characterized in that: The Ti3C2T x The preparation of TiO2 composite particle material includes the following steps: (1) Under water bath conditions, the etchant and the precursor are mixed and stirred, and then centrifuged and washed until the pH of the supernatant is neutral, and the bottom precipitate is collected to obtain Ti3C2T x ; (2) Ti3C2T x After ultrasonic stripping in the intercalant, the mixture was centrifuged at low speed, the supernatant was centrifuged at high speed, and the bottom precipitate was collected after freeze drying to obtain Ti3C2T x Nanosheets; (3) Ti3C2T x The nanosheets were dispersed in water for hydrothermal reaction, and the precipitate was collected by freeze drying to obtain Ti3C2T x @TiO2 composite particle material.

6. The preparation method according to claim 5, characterized in that: In step (1), the temperature of the water bath is 30°C to 50°C; the etchant includes 7mol / L to 10mol / L hydrochloric acid solution and 35% to 45% hydrofluoric acid solution or 0.04g / mL to 0.09g / mL lithium fluoride; the precursor includes any one of titanium silicon carbide and titanium aluminum carbide; the mass volume ratio of the precursor to the etchant is (0.08 to 0.15) g:1mL; the mixing and stirring time is 24h to 48h; the centrifugal speed is 5000rpm to 9000rpm.

7. The preparation method according to claim 5, characterized in that: In step (2), the intercalation agent comprises any one of a 97% to 99% dimethyl sulfoxide solution and a 5% to 25% tetramethylammonium hydroxide solution; the Ti3C2T x The mass volume ratio of the intercalant is (0.07-0.12) g:1 mL; the ultrasonic stripping time is 1 h to 3 h; the low-speed centrifugation includes centrifugation at 1000 rpm to 3000 rpm for 30 min to 60 min; the high-speed centrifugation includes centrifugation at 9000 rpm to 11000 rpm for 30 min to 60 min.

8. The preparation method according to claim 5, characterized in that: In step (3): the Ti3C2T x The mass volume ratio of the nanosheets to the water is (0.017-0.03) g:1 mL; the hydrothermal reaction comprises reacting at 180° C.-200° C. for 12 h-36 h; and the freeze-drying time is 24 h-36 h.

9. A titanium alloy water-based cutting fluid as described in any one of claims 1 to 2, or a titanium alloy water-based cutting fluid prepared by the preparation method as described in any one of claims 3 to 8, which is used in the lubrication process of titanium alloy cutting.